Transcriptome signatures of the lipid metabolism in the liver and partial characterisation of the plasma phospholipidome of a long-distance migratory bird, the Northern Wheatear (Oenanthe oenanthe) - Frias Soler, Roberto Carlos; Wellbrock, Natalie A.; Bindila, Laura; Wink, Michael; Bairlein, Franz (Comparative biochemistry and physiology, 2025)
The Northern Wheatear (Oenanthe oenanthe) is a long-distance migratory bird that has become a model species for the study of the phenomenology and molecular aspects of avian migration. Here, we analysed transcriptomic data related to the lipid metabolism in the liver of wheatears during the development and termination of the migratory fattening. In parallel, we partially characterised their plasma phospholipidome. Based on transcriptomic data, we found evidence of a fine-scale regulation of the lipogenesis/lipolysis rate and over the fatty acid composition during the migratory season. Furthermore, our results suggest a regulated production of oxylipins, signaling lipids derivatives of polyunsaturated fatty acids (PUFAs). Regarding the plasma phospholipid profiling, different lipid species showed a significant differential abundance among migratory stages: lysophosphatidylcholine (LPC 18:0), sphingomyelin (SM 34:1;O2) and phosphatidylinositols (PI 36:4 and PI 38:4). The liver transcriptomic and plasma lipidomic data agree well, showing the relevance of the liver in controlling the lipid metabolism in relation to migration. We hope that the results discussed in this publication would open the door for future functional genetic and metabolic studies regarding avian migration.
Online verfügbar 20 February 2025, Version des Artikels 24 February 2025
Gesehen am 28.07.2025